Aktualisasi Teologis Makna Pembenaran oleh Iman dalam Bingkai Roma 3:28 - Kristiani, Nining; Timisela, Jacob; Tunliu, Misray (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2023)
The Bible emphasizes the importance of salvation. The salvation God has prepared from the beginning reveals God's plans for man. While the doctrine of salvation is very important, it is often debated. Facing contemporary events, the debate among believers becomes a significant topic. The Apostle Paul is the greatest thinker in the New Testament who has understood the person of Jesus Christ and His work, which reveals the secret of justification by faith in the book of Romans through the power of the Holy Spirit. This research discusses the fundamental issue of justification through faith based on the verse of Romans 3:28, which states,